Peran Investasi Perkebunan Terhadap GDP dan Produktivitasnya - Darwati Susilastuti; Wahyu Murti; Bambang Bernanthos (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2023)
Source of Gross Domestic Product (GDP) for the Indonesian among other things that are important isfrom plantation sector. Export-oriented domestic plantation companies, their performance is determined by their productivity and is influenced by many internal and external factors. It is necessary to study role of investment inplantations on gross domestic product and on productivity. Investment policies are needed for sustainable longterm plantation development. This research was purposive by collecting secondary data on the annual time series of Indonesian plantations from 1990 to 2021, using the OLS linear regression data analysis method. The investment variable as an independent variable is regressed against two independent variables, namely plantation GDP and plantation productivity. The conclusion of his research is that investment in plantations has a significant effect and positive on plantation GDP and on plantation productivity. The findings obtained are that Investment plays a large and very strong role in the formation of Plantation GDP and Plantation Productivity and is predicted to take placeinthelong term effect. Further research is suggested to study more deeply the forms and sources of effectiveinvestment.